2021
DOI: 10.1017/jfm.2020.1070
|View full text |Cite
|
Sign up to set email alerts
|

Reynolds stress anisotropy in shock/isotropic turbulence interactions

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The LIA predictions for the overall TKE amplification factor in calorically perfect gases have been previously found to be in fair agreement with numerical simulations 36,38,39,49 and experiments 33 . However, the way LIA predicts the amplified TKE to be partitioned in the streamwise and transverse directions has not been as successful.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The LIA predictions for the overall TKE amplification factor in calorically perfect gases have been previously found to be in fair agreement with numerical simulations 36,38,39,49 and experiments 33 . However, the way LIA predicts the amplified TKE to be partitioned in the streamwise and transverse directions has not been as successful.…”
Section: Discussionsupporting
confidence: 74%
“…However, the way LIA predicts the amplified TKE to be partitioned in the streamwise and transverse directions has not been as successful. In particular, computational and experimental studies at supersonic Mach numbers have often reported Reynolds stress tensors with dominant streamwise contributions, this being an effect typically attributed to convective non-linearities and molecular transport 49 . Whether these discrepancies subside or persist at hypersonic Mach numbers is an open question of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These simulations require advanced computational models and algorithms to capture complex flow physics accurately. Researchers employ numerical techniques such as direct numerical simulations (DNS) [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] and large eddy simulations (LES) [77][78][79] to capture the intricate details of the flow field and provide valuable insights into the underlying physics of STI problems.…”
Section: Motivationmentioning
confidence: 99%
“…the amplification factor becomes a function of only. Furthermore, Grube & Martín (2021) studied the redistribution of energy between the transverse and streamwise Reynolds stresses in the shock–turbulence interaction using LIA and DNS. They developed a model for nonlinear interactions using LIA and the eddy viscosity approximation to quantify the redistribution of energy between transverse and streamwise Reynolds stresses.…”
Section: Introductionmentioning
confidence: 99%